SISTEM AKUAPONIK IKAN LELE DAN KANGKUNG DALAM EMBER SEBAGAI SOLUSI KEMANDIRIAN PANGAN DI MASA PANDEMI - Nurul Fajeriana; Muhammad Arifin Abd Kadir (LP2M Universitas Hasanuddin, 2023)
In 2020, the Coronavirus or Covid-19 outbreak in Indonesia was no exception in Sorong City, West Papua. As a result, the implementation of restricted outdoor activities (lockdown) caused a decline in the economic sector. To anticipate this, it is necessary to make efforts to maximize community activities at home every day so that they remain productive in terms of providing food supplies, where people can grow crops using the Aquaponics system, namely cultivation with a combination of aquatic animals (fish) and plants in one container. The method of implementing this service is by explaining the innovation of aquaculture by cultivating agricultural and fishery plants in one container, then conducting demonstrations on the assembly of Aquaponics in buckets, the correct method of seeding, transferring plant seeds in containers, maintaining fish and water. During the training in Klabulu Village, Malaimsimsa District, the residents who attended were enthusiastic because the costs were similar to using used goods. In addition, two commodities can be cultivated, namely plants and animals, in one container, which significantly supports food independence and nutrition fulfillment even with simple cultivation and without extra care. From the results of this activity, there was an increase in the knowledge, understanding, and skills of participants in aquaponic cultivation and participants who were able to carry out aquaponic cultivation independently and skillfully in their yards as a form of actualization of food independence during a pandemic. — Tahun 2020 menjadi tahun dimana mewabahnya virus Corona atau Covid-19 di Indonesia, tidak terkecuali di Kota Sorong Papua Barat. Akibat dari penerapan kegiatan luar rumah yang dibatasi (lockdown) menyebabkan penurunan dalam sektor ekonomi. Untuk mengantisipasi hal ini, perlu dilakukan upaya untuk memaksimalkan aktivitas masyarakat di rumah setiap harinya agar tetap produktif dalam hal penyediaan pasokan makanan, dimana masyarakat bisa bercocok tanam dengan sistem Akuaponik yakni budidaya dengan perpaduan antara hewan air (ikan) dan juga tanaman dalam satu wadah. Adapun metode pelaksanaan pengabdian ini yakni dengan pemaparan mengenai inovasi budidaya air dengan pembudidayaan tanaman pertanian dan perikanan dalam satu wadah, selanjutnya dilakukan demonstrasi tentang perakitan Akuaponik dalam ember, cara penyemaian benih yang benar, pemindahan bibit tanaman dalam wadah, pemeliharaan ikan dan air. Pada saat pelaksanaan pelatihan di Kelurahan Klabulu Kecamatan Malaimsimsa, warga yang hadir sangat antusias sekali karena selain menggunakan barang bekas juga biaya yang dikeluarkan tidaklah banyak. selain itu ada 2 komoditi yang bisa dibudidayakan yakni tanaman dan hewan dalam satu wadah, dimana sangat menunjang kemandirian pangan dan pemenuhan nutrisi walau dengan budidaya yang sederhana dan tanpa perawatan yang ekstra. Dari hasil kegiatan ini, terjadi peningkatan pengetahuan, pemahaman, dan keterampilan peserta dalam budidaya akuaponik serta peserta/ yang ikut mampu melakukan budidaya akuaponik secara mandiri dan terampil di pekarangan rumah sebagai bentuk aktualisasi kemandirian pangan di saat pandemi.